High-risk Human Papillomavirus Detection in Self-Sampling compared to Clinician Sampling: A Cross-Sectional Study - Andrijono Andrijono; Junita Indarti; Gumilang Gumilang; Kristian Alda (Indonesian Socety of Obstetrics and Gynecology, 2026)
AbstractObjective: To evaluate the diagnostic accuracy of high-risk human papillomavirus (HPV) DNA detection using the Hybrid Capture II assay in self-collected samples compared with clinician-collected samples.Methods: This cross-sectional diagnostic accuracy study enrolled women with abnormal cervical cytology or positive visual inspection with acetic acid (VIA) results at Dr. Cipto Mangunkusumo General Hospital, Jakarta. Participants performed self sampling followed by clinician-collected sampling. High-risk HPV DNA was detected using the Hybrid Capture II assay. Clinician-collected samples served as the reference standard.Results: High-risk HPV prevalence was 44.9%. Self-sampling showed substantial agreement with clinician-collected sampling (κ = 0.76), with 88.41% accuracy, 80.65% sensitivity, 94.74% specificity, 92.59% PPV, and 85.71% NPV.Conclusion: Self-sampling demonstrated comparable diagnostic performance to clinician-collected sampling and may be a reliable alternative for improving cervical cancer screening coverage in Indonesia.Keywords: cervical cancer screening; clinician-collected sampling; high-risk human papillomavirus; Hybrid Capture II; selfsampling